Adverse pregnancy outcomes among women with inflammatory bowel disease: a population based study from England - Abdul Sultan, Alyshah; West, Joe; Ban, Lu; Humes, David; Tata, Laila J.; Fleming, Kate M.; Nelson-Piercy, Catherine; Card, Timothy R. (Lippincott, Williams & Wilkins, 2016)
Background: There is limited contemporary population based evidence on adverse birth outcomes and pregnancy related complications for women with inflammatory bowel disease (IBD). This study provides such estimates of these risks and assesses variation by IBD type and surgical interventions.